Thinking about generations, conjuncturally: A toolkit. Issue 3 (May 2022) - Pina-Cabral, João; Theodossopoulos, Dimitrios
Since the early twentieth century, generation has been a recurrent concept in social analysis. In spite of successive bouts of critique and periods of relative neglect, the category has never been abandoned. In this article, drawing inspiration from a broad range of thinkers – such as José Ortega y Gasset, Karl Mannheim, Antonio Gramsci, Pierre Bourdieu, Raymond Williams and Stuart Hall – we review and fine tune our conceptual toolkit regarding generations, making more explicitly visible its affordances for social analysis in times of crisis. We focus on the problem of intergenerational overlap of contemporaneity and the contradictions that emerge from it. We argue that the notion of coevalness can help us resolve some of these contradictions – for example, the lag between contemporaneity and generational awareness – and introduce, through its horizontal connotations, a decolonising ethical stance. Favouring a processual understanding of generation, we recommend 'conjunctural analysis' as the most flexible analytical framework for resolving the intersectional contradictions and overlaps of generational categorisation.